What is Narrative Research? - Squire, Corinne (The 'What is?' Research Methods Series, 2014)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Narrative research has become a catchword in the social sciences today, promising new fields of inquiry and creative solutions to persistent problems. This book brings together ideas about narrative from a variety of contexts across the social sciences and synthesizes understandings of the field. Rather than focusing on theory, it examines how narrative research is conducted and applied. It operates as a practical introductory guide, basic enough for first-time researchers, but also as a window onto the more complex questions and difficulties that all researchers in this area face. The authors guide readers through current debates about how to obtain and analyse narrative data, about the nature of narrative, the place of the researcher, the limits of researcher interpretations, and the significance of narrative work in applied and in broader political contexts.